Influence of Visual Prism Adaptation on Auditory Space Representation - Klaudia Pochopien; Manfred Fahle (i-Perception, 2017)
Prisms shifting the visual input sideways produce a mismatch between the visual versus felt position of one’s hand. Prism adaptation eliminates this mismatch, realigning hand proprioception with visual input. Whether this realignment concerns exclusively the visuo-(hand)motor system or it generalizes to acoustic inputs is controversial. We here show that there is indeed a slight influence of visual adaptation on the perceived direction of acoustic sources. However, this shift in perceived auditory direction can be fully explained by a subconscious head rotation during prism exposure and by changes in arm proprioception. Hence, prism adaptation does only indirectly generalize to auditory space perception.